Impact of Deep Soil Layer on Terrestrial Microwave Emission for a Bare Agricultural Field - Dogusgen (Erbas), Cihan (Společnost pro radioelektronické inženýrství, 2017)
In this study, we investigated the deep (semi-infinite) soil contribution to the brightness temperature at 1.4 GHz calculated through a modified incoherent radiative transfer model. We reproduced the measured brightness temperature collected by a dual L-band radiometer in a bare agricultural field. We found that exclusion of a semi-infinite soil layer in the incoherent model significantly decreased the brightness temperature when the measurement depth in the model was closer to the emitting depth, which is the first few centimeters from the top of soil. The maximum brightness temperature differences between the cases with and without the semi-infinite layer in the incoherent model were computed to be 6.8444 K, 2.8891 K, 0.2477 K and 0.0004 K for the measurement depths of 4 cm, 5 cm, 8 cm and 16 cm, respectively. Based on a comparison with another coherent radiative transfer model, we observed that inclusion of the deep soil layer significantly improved the precision of the incoherent model regardless of the measurement depth. Our results could be one example of improving the accuracy of radiative transfer models, which might be applied to other radiative transfer models and increase the precision of soil moisture retrieval calculations.
Keywords: Radiative transfer model; soil moisture; bare soil; incoherent model; brightness temperature; microwave radiometry